PERANCANGAN SISTEM INFORMASI INVENTORY BERBASIS WEB PADA CV PRIMA KARYA - Christyani Rannu Keka (2020)
Inventory is a system that is used to manage a variety of inventory of merchandise that is always experiencing changes in the amount and value through sales transactions or purchase transactions. In its application, CV Prima Karya as a trading company still uses a manual system with Microsoft Excel in managing inventory data and data storage. This sometimes causes several problems such as loss of stock data and inefficient data management, and searching for data that requires a long time. Therefore, to reduce these problems, the authors make a web-based inventory information system design that is expected to be a container for managing and storing stock data more efficiently. The author designed a web-based inventory system using the Waterfall method and made a web-based system using codeigniter framework and PHP and MySQL programming languages.